Osteocyte Transcriptome Mapping Identifies a Molecular Landscape Controlling Skeletal Homeostasis and Susceptibility to Skeletal Disease - Youlten, Scott E; Kemp, John P; Logan, John G; Ghirardello, Elena J; Sergio, Claudio M; Dack, Michael R G; Guilfoyle, Siobhan E; Leitch, Victoria D; Butterfield, Natalie C; Komla-Ebri, Davide; Chai, Ryan C; Corr, Alexander P; et al. (bioRxiv, 2020)
Abstract Osteocytes are master regulators of the skeleton. We mapped the transcriptome of osteocytes from different skeletal sites, across age and sexes in mice to reveal genes and molecular programs that control this complex cellular-network. We define an osteocyte transcriptome signature of 1239 genes that distinguishes osteocytes from other cells. 77% have no previously known role in the skeleton and are enriched for genes regulating neuronal network formation, suggesting this program is important in osteocyte communication. We evaluated 19 skeletal parameters in 733 knockout mouse lines and reveal 26 osteocyte transcriptome signature genes that control bone structure and function. We showed osteocyte transcriptome signature genes are enriched for human orthologs that cause monogenic skeletal disorders (P=2.4×10-22) and are associated with the polygenic diseases osteoporosis (P=1.8×10-13) and osteoarthritis (P=1.6×10-7). Thus, we reveal the molecular landscape that regulates osteocyte network formation and function and establish the importance of osteocytes in human skeletal disease. Competing Interest Statement T.G.P is a consultant for Imugene Pty Ltd, an Australian biotech working in cancer immunotherapy. P.I.C has funding from AMGEN for studies of cancer dormancy. Neither competing interests are the subject of this manuscript. Footnotes * ↵27 Co-senior author